MAWAH & CATER DI ACEH STUDI PENINGKATAN KESEJAHTERAAN MASYARAKAT DI ULIM –KAB. PIDIE JAYA - fasya, fasya (Al - Muamalat, 2017)
Mawah and cater are part of local wisdom in Aceh which is a cooperative practice between asset owners and managers/ sharecropper. In the field of agriculture with rice fields as assets, mawah and cater are practiced with the provisions of local customs. This means that the implementation will have a difference in each place, however, the difference in the model of cooperation mawah and cater does not guarantee the proportional and fair benefits for both parties, so that it will impact on their welfare. This study aims to analyze various models of mawah and cater practices that exist in the farming community of Ulim Sub-district of Pidie Jaya Regency and to analyze the impacts on improving the welfare of local farmers. This is a kind of field research with qualitative approach. As a result, this research concludes that there are six models of mawah and one cater model which is practiced in Ulim Sub-district of Pidie Jaya Regency. This study also confirmed the contribution of both cooperations in improving the welfare of local farmers.